ChemInform Abstract: Reaction of Amidoximes with Acetonitrile at High Pressure. Issue 40 (16th September 2016) - Baykov, Sergey V.; Zharov, Aleksey A.; Stashina, Galina A.; Zavarzin, Igor V.; Kofanov, Evgeniy R.
Abstract: affording 1, 2, 4‐oxadiazoles without the use of a catalyst